Preoperative nursing consultation and self-care of cancer patients with respiratory ostomy - Neiva, Renata Otoni; Nogueira, Márcio Correa; Pereira, Adriana Jimenez (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: to demonstrate the influence of the preoperative nursing consultation in the practice of self-care performed by patients with respiratory ostomy at the A.C. Camargo Cancer Center and to describe what are the self-care practices performed and their limiting factors. Method: qualitative, exploratory study, carried out with 7 patients aged 18 years or older, who underwent preoperative nursing consultation, who underwent surgery with the manufacture of a respiratory ostomy and were able to establish verbal communication. Data was collected through semi-structured interviews and a digital recorder and submitted to content analysis. Results: male participants predominated, aged 56 years or over and completed high school. Two analytical categories were identified: “Repercussions of the actions promoted by the preoperative nursing consultation”; and “Obstacles in the search for autonomy in the care of the tracheostomy cannula”. Conclusion: nursing consultation is an important instrument to guide, form bonds and clarify doubts about care with ostomy and respiratory devices, and nursing actions can limit and even prevent the patients from developing their self-care, making it necessary that the therapeutic nursing project is planned to aggregate the patient in this process.